2018
DOI: 10.3390/f10010001
|View full text |Cite
|
Sign up to set email alerts
|

A Review: Individual Tree Species Classification Using Integrated Airborne LiDAR and Optical Imagery with a Focus on the Urban Environment

Abstract: With the significant progress of urbanization, cities and towns are suffering from air pollution, heat island effects, and other environmental problems. Urban vegetation, especially trees, plays a significant role in solving these ecological problems. To maximize services provided by vegetation, urban tree species should be properly selected and optimally arranged. Therefore, accurate classification of tree species in urban environments has become a major issue. In this paper, we reviewed the potential of ligh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
55
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 98 publications
(64 citation statements)
references
References 80 publications
0
55
0
2
Order By: Relevance
“…In the last decade, new approaches emerged to take advantage of the characteristics of active sensors, especially light detection and ranging (LiDAR) systems, which became a trend for tree crown detection [9]. More recently, the authors in [10] concluded that combining LiDAR data with optical imagery generally leads to better classification accuracy. Although this conclusion might be generalized, the authors focused on classifying tree species in urban environments.…”
Section: Introductionmentioning
confidence: 99%
“…In the last decade, new approaches emerged to take advantage of the characteristics of active sensors, especially light detection and ranging (LiDAR) systems, which became a trend for tree crown detection [9]. More recently, the authors in [10] concluded that combining LiDAR data with optical imagery generally leads to better classification accuracy. Although this conclusion might be generalized, the authors focused on classifying tree species in urban environments.…”
Section: Introductionmentioning
confidence: 99%
“…According to the data source used, the existing individual tree species identification can be divided into five categories: multispectral data based, LiDAR data based, multispectral + LiDAR data based, multi-spectral + hyperspectral based, hyperspectral + LiDAR based. The general workflow is to first use ground surveys or high spatial resolution data or high-density LiDAR data to obtain individual tree canopy, and then use universal classification methods to classify individual tree species [2,4].…”
Section: Introductionmentioning
confidence: 99%
“…The fractions of clay, silt, and sand were obtained from the Harmonized World Soil Database (HWSD) constructed by the Food and Agriculture Organization of the United Nations (FAO) and the International Institute [45].All of these spatial datasets were employed in the UTM WGS-84 coordinate system and interpolated to 1 km resolution. Detailed descriptions of datasets were reported elsewhere [46,47].…”
Section: Model Inputsmentioning
confidence: 99%